Pengaruh Kualitas Layanan dan Kualitas Produk terhadap Kepuasan Nasabah Bank Mandiri di Jakarta Kota - Harlim, Nico Sanjaya; Rakhman, Abdullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Banking business behavior must pay attention to the influence of service quality and product quality. Service quality plays an important role in the success of a company to be able to compete which will later create customer satisfaction value. Customer satisfaction will be a guideline to direct the entire organization towards meeting customer needs so that it becomes a source of sustainable competitive advantage. From a customer perspective, many complaints about services and facilities and slow employee service affect customer satisfaction with a product or service. If the company does not anticipate it well, it will backfire on the company itself. The theories used in this research are service quality theory, product quality theory and customer satisfaction theory. There are five indicators that influence service quality, there are six indicators that influence product quality, and there are three indicators that influence customer satisfaction. The method used in this research is Non Probability sampling by collecting data through questionnaires distributed to 100 respondents who are Bank Mandiri customers in Jakarta City. To determine the sample, the method used was Non Probability sampling with Incidental sampling technique. The measuring instruments used in this research are validity tests, reliability tests, arithmetic averages, percentage analysis, scale ranges, classical assumption tests, and multiple regression analysis. The tool used for analysis is SPSS 26. The results of this study indicate that service quality and product quality have a positive and significant effect on customer satisfaction at Bank Mandiri in Jakarta Kota.